Efek Merger Dan Akuisisi Terhadap Kinerja Keuangan Perusahaan Go Public - Mia Kurniati; Asmirawati Asmirawati (JPS (Jurnal Perbankan Syariah), 2022)
This study aims to show the financial performance of companies listed on the Indonesian stock exchange before and after mergers and acquisitions. This study uses a quantitative approach, with the population being all companies listed on the Indonesian stock exchange. The sampling technique uses purposive sampling to obtain a total sample of 45 companies. This study uses six financial ratios, namely, return on equity (ROA), net profit margin (NPM), quick ratio (QR), debt to asset ratio (DAR), total asset turnover (TATO), and price earning ratio (PER). Data analysis using the Wilcoxon rank test. The results showed significant differences in the ROA and NPM values before and after mergers and acquisitions were carried out. Then the value of QR, DAR, TATO, and PER is no significant difference before and after mergers and acquisitions. This study can be a reference for company owners in making decisions for mergers and acquisitions of companies.